Adherence of human peripheral blood lymphocytes to measles-virus infected cells: modulation by solubilized rhesus erythrocyte membranes and carbohydrates. - Bankhurst, A D (1979)
The adherence of human peripheral blood lymphocytes to HeLa cells persistently infected with measles virus (HeLa-K11) was studied. The following data were observed. (i) The proportion of HeLa-K11 cells with adherent human peripheral blood lymphocytes of rhesus monkey erythrocytes was similar over a wide range of ratios of HeLa-K11 cells to lymphocytes or erythrocytes. (ii) The great majority of human peripheral blood lymphocytes and erythrocytes reacted with the same HeLa-K11 cell (iii). The adherence of lymphocytes or erythrocytes to HeLa-K11 cells was blocked by rabbit anti-measles virus antibody or solubilized monkey erythrocyte membranes. The pretreatment of erythrocytes or lymphocytes with receptor-destroying enzyme did not alter their adherence properties. (iv) The pattern of inhibition observed with several carbohydrates was similar in both the erythrocyte and the lymphocyte adherence assays. These data are consistent with the possibility that the receptor present on both rhesus monkey erythrocytes and human lymphocytes has similar specificities and biochemical composition.